Comparative Study Between Three Intravenous Drugs Thiopentone Sodium, Propofol and Midazolam: Study of 100 Cases and Critical Review - Mondol, SK; Rahim, MA (TAJ: Journal of Teachers Association, 2009)
Intravenous anesthesia became possible with drugs available since 1930 and the concept rapidly became popular with patients and anaesthetists. From the patient's point of view it had the advantage of producing rapid loss of consciousness without excitement, distress, or the sensation of smothering often produced by a tightly pressed facemask. For the anesthetist, there was the predictable anaesthesia which was ideally rapid in onset and without coughing or movements. Thiopentone sodium, propofol and midazolam have been used in our comparative clinical study (About 100 cases) as an intravenous anaesthetic agent. Our clinical study was into three aged groups such as neonates & children (40 cases), middle aged (40 cases) and elderly (20 cases). 100 cases were divided into paediatric cases, in outpatient procedures, in neurosurgical cases, in geriatric anaesthesia, in obstetric cases. In our comparative study, we have seen when propofol used for induction of anaesthesia in briefer procedures, results in a significantly quicker recovery and an earlier return of psychomotor function as compared with thiopentone and midazolam irrespective of the agent used for maintenance of anaesthesia. doi: 10.3329/taj.v20i1.3086 TAJ 2007; 20(1): 28-35